Perancangan Sistem Informasi Peminjaman Buku Perpustakaan SMAN 2 Cikarang Utara Menggunakan PHP dan MySQL - U. Darmanto Soer; Wahyudi Wahyudi (Jurnal SIGMA, 2021)
Library SMAN 2 North Cikarang not using the means of internet or computer and still use manual methods to manage the catalog of books and other administration. Due to its management is considerable and complicated as well as to address some of the issues that arise over the solutions that can be applied is to Designing Information System Application Library Books At SMAN 2 North Cikarang. To keep books neatly arranged, organized by category respectively, and can increase the accuracy of the low in the recording process of borrowing books can be overcome with the new system. Development of the proposed system is done in two stages, namely, the stage of data collection methodology comprised interviews, field studies, literature studies and the next stage is the development of software with waterfall method, using the Application Programming PHP, and MySQL as the database server. For system design tool using Data Flow Diagrams (DFD), Entity Relation Diagram (ERD), Data Dictionary, as well as hardware and software specifications. With the Book Lending Library Information System, is expected to assist officers in serving the transaction Library borrowing and returning library books. And makes it easy for members of the Library make the process of borrowing and returning books at the Library of SMAN 2 North Cikarang. Keywords: Information Systems, Web, Library, Waterfall, PHP, MySQL